Local Antibiotic Delivery Systems in Diabetic Foot Osteomyelitis: Time for One Step Beyond?. (March 2015) - Panagopoulos, Periklis; Drosos, Georgios; Maltezos, Efstratios; Papanas, Nikolaos
In patients with diabetes mellitus, osteomyelitis is a severe, difficult-to-treat form of foot infection. In the management of diabetic foot osteomyelitis, carriers for local delivery of antimicrobial agents have begun to be tried, in an attempt to provide high local antibiotic concentrations. Randomized clinical trials are now expected to clarify when this new approach should be used and how it can be integrated into the overall therapeutic strategy for diabetic foot osteomyelitis.